Maladaptive Denial of Severe Pain and Acute Orthopedic Injuries in a Patient With a Schizoaffective Disorder - Prigatano, George P.; McKnight, Curtis; Andrews, Megan; Caplan, Jason (Frontiers in Psychology, 2020)
Persistent denial of severe and acute pain following orthopedic injuries has not been previously reported. We present a case of a 24-year-old woman with a history of schizoaffective disorder who suffered severe pain secondary to acute orthopedic injuries who insisted, “I am fine! There is nothing wrong with me.” Her maladaptive denial resulted in an initial refusal of necessary medical/surgical care, but she eventually accepted the necessary treatments despite her persistent belief she did not need such care. Her verbalizations and behaviors were characterized by active avoidance and angry reactions when a consulting psychiatrist spoke to her regarding her clinical condition. A modified version of the Conscious Avoidance subscale of the Denial of Illness Questionnaire was useful in measuring the severity level of her denial. This case report suggests that the behavioral features of psychological denial appear different from those associated impaired self-awareness secondary to an underlying brain disorder.